Spatial evaluation of the impact of a climate change participatory extension programme on the uptake of soil management practices. (20th June 2021) - Yang, Wei; Knook, Jorie
Abstract : Participatory extension programmes (PEPs) are a popular policy tool to stimulate the uptake of climate change mitigation practices on a farm level. Given the public investment in PEPs, reliable evaluation is important. However, few studies evaluate climate change PEPs. Moreover, the evaluations conducted so far do not correctly account for potential spatial effects, such as the influence of neighbouring farms on PEP participation. Therefore, this paper estimates the impact of PEP participation on the uptake of a climate change mitigation practice and soil management, and identifies the importance of spatial effects on PEP participation. A spatial propensity score matching method is applied to a dataset from Scotland, consisting of 134 PEP and 184 control farmers. The results show that PEP participation facilitates the uptake of soil management practices and that spatial dependence exists in farmers' decision‐making, indicating the need for the inclusion of spatial factors. This study contributes to the current literature by combining spatial econometric analysis and propensity score matching to conduct a quantitative evaluation of a climate change PEP. The evaluation methodology provides decision‐makers with reliable insights into the potential contribution of PEPs towards climate change mitigation targets.